2017
DOI: 10.1111/echo.13595
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial strain predicts hemodynamic parameters in cardiovascular patients

Abstract: In a cohort of patients with a broad spectrum of cardiovascular diseases LA strain shows a valuable prediction of hemodynamic parameters, specifically LV filling pressures, in the presence of SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
0
25
0
2
Order By: Relevance
“…Nine of the 18 studies reported LA function with 653 patients (Hozo et al ., ; Rutter & Gatsonis, ; Askenazi et al ., ; Tabata et al ., ; Cameli et al ., ; Rafique et al ., ; Estep et al ., ; Kawasaki et al ., ; Hewing et al ., ), and 50% of them had heart failure (HF). Patients included in these studies were younger compared to those with anatomical LA measurements (63 ± 10 versus 69 ± 10 years, P = 0·001), but there was no difference in LVEF (47·5 ± 10·5 versus 50·3 ± 12·7%, P = 0·67, Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of the 18 studies reported LA function with 653 patients (Hozo et al ., ; Rutter & Gatsonis, ; Askenazi et al ., ; Tabata et al ., ; Cameli et al ., ; Rafique et al ., ; Estep et al ., ; Kawasaki et al ., ; Hewing et al ., ), and 50% of them had heart failure (HF). Patients included in these studies were younger compared to those with anatomical LA measurements (63 ± 10 versus 69 ± 10 years, P = 0·001), but there was no difference in LVEF (47·5 ± 10·5 versus 50·3 ± 12·7%, P = 0·67, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Raised LA pressure, irrespective of its aetiology, causes increased wall stress which leads to chamber dilatation and thinning of the atrial wall (Christensen et al ., ). Myocardial stretch and increase in LA cavity volume is a feature of the response of thin myocardium to pressure overload in contrast to the thick myocardium that gets thicker as is the case in the left ventricle (Hewing et al ., ). Increases in LA volume has also been shown to reflect the duration and severity of raised LA pressure (Hummel et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A recent meta‐analysis identified E/e' as the most robust parameter within the criteria in determining invasive LV filling pressures, though showing only a modest correlation (r = 0.56) . LA strain has previously shown ability to predict raised resting PCWP in HF with reduced ejection fraction, cardiovascular patients, and heart transplant recipients . Similarly, LA reservoir strain is able to identify patients with elevated resting PCWP > 15 mmHg .…”
Section: Discussionmentioning
confidence: 99%
“…Exercise echocardiography should be considered more often because of the higher sensitivity it achieves. Additionally, a number of recent studies have now explored the use of strain echocardiography for characterization of diastolic function . Whether this approach will eventually be superior to Doppler‐based methods remains to be shown.…”
Section: Discussionmentioning
confidence: 99%